Quantum Analogues: From Phase Transitions to Black Holes and Cosmology - Unruh, William; Schützhold, Ralf (Lecture Notes in Physics, 2007)
Recently, analogies between laboratory physics (e.g. quantum optics and condensed matter) and gravitational/cosmological phenomena such as black holes have attracted an increasing interest. Especially in view of the tremendous progress of the experimental capabilities (e.g. regarding superfluids such as liquid Helium or gaseous Bose-Einstein condensates), exotic quantum effects such as Hawking radiation might come into reach for the first time. This book contains a series of selected lectures devoted to this new and rapidly developing interdisciplinary field of research. Various analogies connecting (apparently) different areas in physics are presented in order to bridge the gap between them and to provide an alternative point of view - which will provide a deeper insight for graduate students as well as senior scientists.